Reinforcing steel bar anticorrosive material based on microorganism induced mineralization as well as preparation method and application of reinforcing steel bar anticorrosive material
Through the formation of biomineralized films based on the anticorrosion materials of reinforced bars based on microbial mineralization, the problem of corrosion of steel bars in harsh marine environments is solved, economical and environmentally friendly steel bar protection is achieved, and the durability and service life of the structure are improved.
Patent Information
- Application Number
- CN202411665823.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-21
AI Technical Summary
In harsh marine environments, reinforced concrete structures are prone to cracking, resulting in carbonization and erosion of the steel bars, affecting the durability and safety of the structure. Existing protection measures are costly and not environmentally friendly.
Using reinforced bar anticorrosion materials based on microbial induced mineralization, a layer of biomineralized film is formed by activating urea-shaped bacteria and adding urea, calcium sources and other components to provide a physical barrier to prevent corrosion.
This method is not only economical and environmentally friendly, has mild reaction conditions, and is compatible with the concrete matrix. It can effectively inhibit the contact between chloride salt and steel bars, and repair the microcracks of concrete through bacterial filling, thereby improving the durability and service life of the reinforced concrete structure.
Smart Images

Figure CN119662061A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of steel bar corrosion resistance, and in particular to a steel bar anti-corrosion material based on microbial induced mineralization, a preparation method and application thereof. Background Art
[0002] Reinforced concrete is widely used in important civil engineering structures such as buildings, bridges, tunnels, and dams. However, in harsh underground service environments such as offshore and oceans, cracking of concrete structures is relatively common. Once the concrete cracks, the exposed steel bars are easily corroded by carbonization and chloride ions in the environment, resulting in the destruction of the passivation film on the surface of the steel bars and subsequent corrosion, which seriously affects the durability and safety of the structure. Therefore, it is crucial to adopt effective steel protection measures.
[0003] Currently, steel bars are usually protected by organic coatings, rust inhibitors, electrochemical protection, etc. These measures are not only costly, but also not environmentally friendly and prone to pollution. Summary of the invention
[0004] The present invention is made to solve the above-mentioned problems, and aims to provide a steel bar anti-corrosion material based on microbial induced mineralization, a preparation method and application thereof.
[0005] The present invention provides a steel bar anti-corrosion material based on microbial induced mineralization, which has the following characteristics: urea-lytic bacteria with the ability to induce mineralization, nutrients, urea and a calcium source, wherein the nutrients include 4-6 g / L soy protein and 15-20 g / L casein.
[0006] The steel bar anticorrosive material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the urealytic bacteria is a combination of one or more of Bacillus pasteurianus, Bacillus sphaericus, and seawater spore Sarcina that have the function of secreting urease, and the concentration of the urealytic bacteria is 9×10 7 -6×10 9 cells / mL.
[0007] The steel bar anti-corrosion material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the urea concentration is 20-25 g / L.
[0008] The steel bar anti-corrosion material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the calcium source is 20-50 g / L calcium acetate monohydrate or 20-50 g / L calcium nitrate tetrahydrate.
[0009] The steel bar anti-corrosion material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the mass ratio of urea to calcium source is 1:(1-2).
[0010] The present invention also provides a method for preparing a steel bar anti-corrosion material based on microbial induced mineralization, which has the following characteristics: wherein the preparation method is specifically as follows: urea-lytic bacteria with the ability to induce mineralization are activated and cultured, and then collected by centrifugation and added to nutrients, urea and calcium source solution weighed according to the mass ratio, and stirred evenly with a glass rod to complete the preparation.
[0011] The method for preparing the steel bar anticorrosive material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the activation culture time is 24-48 hours.
[0012] The present invention also provides an application of a steel bar anti-corrosion material based on microbial induced mineralization, which has the following characteristics: wherein, the steel bar after rust removal and grinding is immersed in the steel bar anti-corrosion material, bacteria form a layer of biomineralization film on the surface of the steel bar, and then the steel bar after surface mineralization treatment is pre-embedded in concrete, and the biomineralization film can play a physical barrier role to provide corrosion protection for the steel bar.
[0013] The application of the steel bar anti-corrosion material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the immersion time is 24-72 hours, and the immersion temperature is 20-30°C.
[0014] The application of the steel bar anticorrosive material based on microbial induced mineralization provided by the present invention may also have the following characteristics: wherein the thickness of the biomineralization film is 30-60 μm.
[0015] Functions and Effects of the Invention
[0016] According to the steel bar anti-corrosion material, preparation method and application thereof based on microbial induced mineralization involved in the present invention, the present invention utilizes microbial induced mineralization to achieve metal corrosion inhibition, which is not only economical and environmentally friendly, but also has good compatibility with the concrete matrix due to its mild reaction conditions. It has been widely used in the field of civil engineering for structural crack repair, concrete surface protection, etc. Therefore, microbial induced mineralization is utilized to form a biomineralized film composed of calcium carbonate, bacteria and bacterial extracellular polymers EPS on the surface of the steel bar. On the one hand, it can effectively inhibit the contact between chloride salts and steel bars. On the other hand, the bacteria in the film layer can also fill and repair the microcracks and pores in the concrete after the concrete cracks, making the matrix more compact, thereby further hindering the chloride salts and other corrosive media from entering and corroding the steel bars, achieving the effect of synergistic protection, improving the durability of reinforced concrete structures, and extending the service life of the structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM and EDS images of the microbial mineralization products of the present invention;
[0018] Figure 2is the XRD pattern of the microbial mineralization product of the present invention;
[0019] Figure 3 is the FT-IR spectrum of the microbial mineralization product of the present invention;
[0020] Figure 4 The optical microscope images of the steel bar surfaces of the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2, and Comparative Example 2 after being immersed in 0.35% NaCl and 3.5% NaCl solutions for 12 days respectively;
[0021] Figure 5 The corrosion inhibition efficiency diagram of the steel bars after the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2 and Comparative Example 2 were immersed in 0.35% NaCl and 3.5% NaCl solutions for 12 days respectively;
[0022] Figure 6 Electrochemical impedance spectra of the steel bars of the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2, and Comparative Example 2 after being immersed in 0.35% NaCl and 3.5% NaCl solutions for 12 days respectively; and
[0023] Figure 7 The equivalent circuit diagram used for fitting the EIS results of Example 1, Comparative Example 1, Example 2, and Comparative Example 2. DETAILED DESCRIPTION
[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments and the accompanying drawings specifically illustrate the steel bar anti-corrosion material based on microbial induced mineralization, the preparation method and the application thereof of the present invention.
[0025] Example 1
[0026] Sporosarcina pasteurii was activated and cultured for 24 hours, collected by centrifugation, diluted with sterile saline (0.9% NaCl solution), and then mixed with casein, soy protein, urea, and calcium nitrate tetrahydrate solution to obtain a solution containing 15 g / L casein, 4 g / L soy protein, 20 g / L urea, 20 g / L calcium nitrate tetrahydrate, and a bacterial concentration of 9 × 10 7 cells / mL mixed solution, that is, microbial mineralizer mixed solution.
[0027] The electrodes were made of Q235 steel bars with a diameter of 6 mm and a length of 60 mm. After rust removal and grinding, copper wires were connected at both ends. The electrodes were encapsulated with epoxy resin and the middle section of the steel bars was exposed for 30 mm, with an exposed area of about 7.54 cm. 2, soak the prepared steel bar electrode in the microbial mineralizer mixture for 48 hours at a temperature of 30° C. After soaking, take out the steel bar electrode with surface mineralization treatment.
[0028] A water-cement ratio of 0.6 and a sand-cement ratio of 3.0 were used to prepare concrete specimens with a diameter of 80 mm and a height of 20 mm. The steel electrodes after surface mineralization treatment were pre-embedded. After 28 days of curing under standard curing conditions, in order to simulate the cracking phenomenon of concrete in the actual environment, the test blocks after curing were cracked using a pressure testing machine. The cracked reinforced concrete specimens were immersed in 0.35% NaCl solution for 12 days at a temperature of 20°C.
[0029] Embodiment 2:
[0030] Based on the test procedure of Example 1, "immersing the cracked reinforced concrete specimen in a 0.35% NaCl solution" is replaced by "immersing the cracked reinforced concrete specimen in a 3.5% NaCl solution".
[0031] Comparative Example 1:
[0032] Based on the test procedure of Example 1, the steel bars used were not subjected to surface mineralization treatment.
[0033] Comparative Example 2:
[0034] Based on the test steps of Example 1, "immersing the cracked reinforced concrete sample in a 0.35% NaCl solution" is replaced by "immersing the cracked reinforced concrete sample in a 3.5% NaCl solution", and the steel bars used are not mineralized.
[0035] Electrochemical testing:
[0036] (1) SEM-EDS results The surface morphology of microbial mineralization products was photographed using a ZEISS GeminiSEM 300 scanning electron microscope (SEM), and the elemental composition of the surface products was analyzed using an energy dispersive spectrometer (EDS).
[0037] (2) XRD patterns were obtained by using a Bruker D8Advance X-ray diffractometer (XRD) to characterize the crystal structure of biomineralization products at a test angle of 5°-90°.
[0038] (3) FT-IR spectra were obtained by using a ThermoScientific Nicolet iS5 Fourier transform infrared spectrometer (FT-IR) to characterize the internal functional groups of biomineralization products in the wavenumber range of 4000–400 cm -1 .
[0039] (4) The optical microscope image was obtained by taking a digital optical microscope of the steel bar sample after being immersed in chloride salt for 12 days.
[0040] (5) The electrochemical results were obtained by using a Corrtest CS350 electrochemical workstation to test steel bar samples after immersion in chloride salt for 12 days. The Tafel weak polarization test was performed at a scan rate of 0.167 mV / s to test the steel bar relative to the corrosion potential ±50 mV. The AC perturbation amplitude of the electrochemical impedance spectroscopy was 10 mV and the frequency range was 10 -2 Up to 10 5 Hz.
[0041] The test results are as follows:
[0042] Figure 1 The following are SEM and EDS images of the microbial mineralization products of the present invention.
[0043] like Figure 1 As shown in the SEM-EDS figure, Figure 1 It shows that a dense biomineralization film is formed on the surface of the steel bar. The product is elliptical or spherical particles. The EDS results show that it is CaCO3. At the same time, traces of rod-shaped bacteria are found (indicated by the white arrow). The detected N element shows the presence of organic matter in the formed biomineralization film.
[0044] Figure 2 The XRD pattern of the microbial mineralization product of the present invention is shown in FIG.
[0045] like Figure 2 As shown in the XRD pattern, Figure 2 Results Compared with the standard PDF card, the product was mainly composed of calcite and vaterite.
[0046] Figure 3 FT-IR spectrum of the microbial mineralization product of the present invention.
[0047] like Figure 3 The FT-IR spectrum shows that Figure 3 The results showed that the mineralized product contained calcite and vaterite, which was consistent with the XRD results. -1 An absorption peak caused by the stretching vibration of alkyl (-CH2 or -CH3) was observed, which was speculated to be bacterial extracellular polymer substances (EPS), indicating that the mineralization product formed was an organic-inorganic hybrid membrane.
[0048] Figure 4 These are optical microscope images of the steel bar surfaces of the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2, and Comparative Example 2 after being immersed in a chloride salt solution for 12 days.
[0049] Optical microscope image: Figure 4 It can be seen that both Comparative Examples 1 and 2 show obvious corrosion, while the steel bars of Examples 1 and 2 have obvious deposition of white mineralized products on their surfaces and the corrosion is significantly reduced, indicating that the present invention can well inhibit steel bar corrosion.
[0050] Figure 5 This is a graph showing the corrosion inhibition efficiency of steel bars after the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2, and Comparative Example 2 were immersed in a chloride salt solution for 12 days.
[0051] Corrosion inhibition efficiency: The Tafel weak polarization test results are fitted with the CS Studio software that comes with the Corrtest electrochemical workstation to obtain the corrosion current density, and the corresponding inhibition efficiency is calculated using the formula in and i corr Respectively, the steel corrosion current density of the comparative example and the embodiment, μA·cm -2 .from Figure 5 It can be seen that after immersion test in chlorine-containing corrosion environment for 12 days, the biomineralized membrane in the embodiment can still exert an inhibition efficiency of about 70%, but with the increase of chloride salt concentration, the corrosion inhibition efficiency decreases.
[0052] Figure 6 Electrochemical impedance spectra of the steel bars of the cracked reinforced concrete specimens of Example 1, Comparative Example 1, Example 2 and Comparative Example 2 after being immersed in a chloride salt solution for 12 days.
[0053] Electrochemical impedance spectroscopy: Figure 6 It can be seen that after being immersed in 0.35% NaCl solution and 3.5% NaCl solution for 12 days, respectively, the capacitive reactance arc of the steel bars in Examples 1 and 2 is significantly greater than that in Comparative Examples 1 and 2, indicating that the corrosion resistance of the steel bars is improved.
[0054] Table 1
[0055] Example <![CDATA[R c (Ω·cm 2 )]]> <![CDATA[R f (Ω·cm 2 )]]> <![CDATA[R ct (kΩ·cm 2 )]]> Equivalent Circuit Example 1 162.5 164.6 15744 (a) Comparative Example 1 61.38 85.61 108.1 (b) Example 2 167.1 168.5 4152 (a) Comparative Example 2 77.93 97.73 45.2 (b)
[0056] Figure 7 The equivalent circuit diagram used for fitting the EIS results of Example 1, Comparative Example 1, Example 2, and Comparative Example 2. Table 1 shows the EIS fitting results of the steel bars after 12 days of immersion test.
[0057] like Figure 7 As shown, the EIS results were fitted using an equivalent circuit diagram using Zview software. The fitting results are shown in Table 1. It can be found that compared with Comparative Examples 1 and 2, Examples 1 and 2 not only have a lower charge transfer resistance R ct and film resistance R fIt is much higher than the control ratio, which fully demonstrates that the biomineralization film effectively inhibits the contact between chloride salt and steel bars and plays a role in corrosion protection. The resistance value of the concrete protective layer R c It is also much higher than the control ratio, which shows that the bacteria in the biomineralization membrane can fill and repair the micro cracks and pores in the concrete, making the matrix denser, thereby further preventing corrosive media such as chloride salts from entering and corroding the steel bars, achieving a long-term synergistic protection effect.
[0058] Functions and Effects of the Embodiments
[0059] According to the steel bar anti-corrosion material, preparation method and application thereof based on microbial induced mineralization involved in the present invention, the present invention utilizes microbial induced mineralization to achieve metal corrosion inhibition, which is not only economical and environmentally friendly, but also has good compatibility with the concrete matrix due to its mild reaction conditions. It has been widely used in the field of civil engineering for structural crack repair, concrete surface protection, etc. Therefore, microbial induced mineralization is utilized to form a biomineralized film composed of calcium carbonate, bacteria and bacterial extracellular polymers EPS on the surface of the steel bar. On the one hand, it can effectively inhibit the contact between chloride salts and steel bars. On the other hand, the bacteria in the film layer can also fill and repair the microcracks and pores in the concrete after the concrete cracks, making the matrix more compact, thereby further hindering the corrosion media such as chloride salts from entering and corroding the steel bars, achieving the effect of synergistic protection, improving the durability of reinforced concrete structures, and extending the service life of the structures.
[0060] Compared with traditional steel protection measures such as rust inhibitors and organic coatings, the microbial induced mineralization of the present invention has better compatibility with the concrete matrix, avoids the negative impact of the addition of organic coatings, rust inhibitors, etc. on the working performance and mechanical properties of concrete, and is beneficial to improving the durability of reinforced concrete structures.
[0061] The invention is a steel bar anti-corrosion material that is harmless to the natural environment. The microorganism-induced mineralization reduces the harm of harmful rust inhibitors and organic coatings to the environment, and is a green and environmentally friendly anti-corrosion material.
[0062] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A steel bar anti-corrosion material based on microbial induced mineralization, characterized in that: include: Ureaplasmic bacteria with the ability to induce mineralization, nutrients, urea and a calcium source, wherein the nutrients include 4-6 g / L soy protein and 15-20 g / L casein.
2. The steel bar anticorrosive material based on microbial induced mineralization according to claim 1, characterized in that: in, The urealytic bacteria is a combination of one or more of Bacillus pasteurianus, Bacillus sphaericus, and Sporosarcina marinum, which have the function of secreting urease. The concentration of the urealytic bacteria is 9×10 7 -6×10 9 cells / mL.
3. The steel bar anticorrosive material based on microbial induced mineralization according to claim 1, characterized in that: in, The urea concentration is 20-25 g / L.
4. The steel bar anticorrosive material based on microbial induced mineralization according to claim 1, characterized in that: in, The calcium source is 20-50 g / L calcium acetate monohydrate or 20-50 g / L calcium nitrate tetrahydrate.
5. The steel bar anticorrosive material based on microbial induced mineralization according to claim 1, characterized in that: in, The mass ratio of the urea to the calcium source is 1:(1-2).
6. The steel bar anticorrosive material based on microbial induced mineralization according to claim 1, characterized in that: The preparation method of the antiseptic material based on microbial induced mineralization is specifically as follows: The urea-lytic bacteria with the ability to induce mineralization are activated and cultured, collected by centrifugation, added to the nutrients, urea and calcium source solution weighed according to the mass ratio, and stirred evenly with a glass rod to complete the preparation.
7. The method for preparing an antiseptic material based on microbial induced mineralization according to claim 6, characterized in that: in, The activation culture time is 24-48h.
8. An application of the steel bar anticorrosion material based on microbial induced mineralization as claimed in claims 1 to 7, characterized in that: The steel bars that have been rust-removed and polished are immersed in the steel bar anti-corrosion material, and bacteria form a layer of biomineralization film on the surface of the steel bars. The steel bars that have been surface mineralized are then pre-embedded in concrete. The biomineralization film can act as a physical barrier to provide corrosion protection for the steel bars.
9. The method for preparing an antiseptic material based on microbial induced mineralization according to claim 8, characterized in that: in, The soaking time is 24-72 hours, and the soaking temperature is 20-30°C.
10. The method for preparing an antiseptic material based on microbial induced mineralization according to claim 8, characterized in that: in, The thickness of the biomineralization membrane is 30-60 μm.
Citation Information
Patent Citations
Method for preparing calcium carbonate by simultaneous mineralization of two microorganisms
CN108220380A
Steel anti-corrosion method based on microbial technology
CN112680733A
Biological material for rapidly repairing concrete microcracks and preparation method thereof
CN115626790A